Evaluation of Faba Beans, White Lupins and Peas as Protein Sources in Broiler Diets - Nalle, C.L.; Ravindran, V.; Ravindran, G. (International Journal of Poultry Science, 2010)
The aim of the present study was to evaluate the effect of the inclusion of faba beans (Vicia faba), white lupins (Lupinus albus) and peas (Pisum sativum) in two different basal diets on the performance, digestive tract development and carcass characteristics of broilers housed in floor pens over a 35 d grow-out period. The experimental design was a 2 x 4 factorial arrangement of treatments which evaluated two basal wheat-soy diets (with or without meat meal) and legume grains (no legume grain, or faba beans, white lupins and peas at 200 g/kg inclusion). All diets were formulated to contain similar levels of metabolizable energy and digestible amino acids. A 3-phase feeding programme (starter, grower and finisher) was employed. The starter, grower and finisher diets were offered from day 1-7, 8-21 and 22-35, respectively. During the starter period, legume x meat meal interaction was significant (p